Folic acid supplementation and dietary folate intake, and risk of preeclampsia - Wang, Y (Eur J Clin Nutr, 2015)
BACKGROUND/OBJECTIVES: Folic acid supplementation has been suggested to reduce the risk of preeclampsia. However, results from few epidemiologic studies have been inconclusive. We investigated the hypothesis that folic acid supplementation and dietary folate intake before conception and during pregnancy reduce the risk of preeclampsia. SUBJECTS/METHODS: A birth cohort study was conducted in 2010–2012 at the Gansu Provincial Maternity & Child Care Hospital in Lanzhou, China. A total of 10 041 pregnant women without chronic hypertension or gestational hypertension were enrolled. RESULTS: Compared with nonusers, folic acid supplement users had a reduced risk of preeclampsia (OR = 0.61, 95% CI: 0.43–0.87). A significant dose–response of duration of use was observed among women who used folic acid supplemention during pregnancy only (P-trend = 0.007). The reduced risk associated with folic acid supplement was similar for mild or severe preeclampsia and for early- or late-onset preeclampsia, although the statistical significant associations were only observed for mild (OR = 0.50, 95% CI: 0.30–0.81) and late-onset (OR = 0.60, 95% CI: 0.42–0.86) preeclampsia. The reduced risk associated with dietary folate intake during pregnancy was only seen for severe preeclampsia (OR = 0.52, 95% CI: 0.31–0.87, for the highest quartile of dietary folate intake compared with the lowest). CONCLUSIONS: Our study results suggest that folic acid supplementation and higher dietary folate intake during pregnancy reduce the risk of preeclampsia. Future studies are needed to confirm the associations.